Mechanisms for Reading Rhetorical Heritage: Vision and Approach - Guiza, Aissa (Milev Journal of Research and Studies, 2021)
Linguists in the modern and contemporary era have paid attention to linguistic [lexical - grammatical and rhetorical ... In their reading of the rhetorical lesson, the scholars were influenced by the quotations of the historical method, or by the modern linguistic lesson. Hence several readings have appeared that their owners have attempted to revisit this heritage. Hence, this article explores the fact that it monitors these readings, explaining the reasons that prompted the linguists to put forward ideas for renewing the Arabic rhetoric, and answering a fundamental question that is the extent to which those attempts to address the limitations of rhetoric have succeeded